1994
DOI: 10.1037/0022-0167.41.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Cultural mistrust, opinions about mental illness, and Black students' attitudes toward seeking psychological help from White counselors.

Abstract: In this study, the relationship among mistrust of Whites, opinions about mental illness, and help-seeking attitudes among Black college students (N = 105) was examined. Participants completed the Cultural Mistrust Inventory, the Opinions About Mental Illness Scale, the Help-Seeking Attitude Scale, and the Reid-Gundlach Social Service Satisfaction Scale. The hypothesis that higher levels of cultural mistrust would predict negative help-seeking attitudes was generally supported through regression analyses. Great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
155
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 38 publications
(47 reference statements)
5
155
2
Order By: Relevance
“…Previous studies assumed that prior negative attitudes 7 among African Americans and mistrust 8 of White providers accounted for lower use of services at times of need. In contrast, our results suggest that African Americans have comparable and, in most instances, more favorable attitudes toward seeking care for their mental illness than do their White counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies assumed that prior negative attitudes 7 among African Americans and mistrust 8 of White providers accounted for lower use of services at times of need. In contrast, our results suggest that African Americans have comparable and, in most instances, more favorable attitudes toward seeking care for their mental illness than do their White counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, African Americans may have a higher prevalence of mental illness because they tend to be poorer than Whites. 6,7 Along with economic barriers, African Americans may have prior negative attitudes 7 toward seeking care, which may explain their mistrust of White providers 8 and subsequent lower use of mental health services, particularly at times of need.…”
mentioning
confidence: 99%
“…Issues identified as barriers to treatment seeking have been noted previously in the literature. Despite acknowledgement of the need for services and perhaps consistent with the focus on serious and persistent mental illness, participants noted that stigma, costs, and knowledge of available services affected treatment seeking (Mutchler & Burr, 1991;Nickerson et al, 1994;Silva de Crane & Spielberger, 1981;Terrell & Terrell, 1984).…”
Section: Applications and Implications For Clinical Practicementioning
confidence: 99%
“…Terrell and Terrell (1984) suggested that African Americans who rated high in mistrust were more likely to terminate therapy prematurely. Nickerson, Helms, and Terrell (1994) reported that African American students who rated high in cultural mistrust of White Americans were less likely to visit the campus counseling center. Thus, issues of trust may be relevant to African Americans' attitudes toward mental health and service usage.…”
mentioning
confidence: 99%
“…This predominant emphasis on the risks of self-disclosure appears to be a common experienceevidence suggests that clients report feeling anxious and vulnerable before self-disclosure (Farber et al 2004). Moreover, for ethnic minority and immigrant clients, beliefs regarding self-disclosure may be even more convoluted due to factors such as unfamiliarity with mainstream psychotherapy's emphasis on client self-disclosure, cultural mistrust toward providers, and stigmatizing beliefs related to seeking help for emotional distress (Nickerson et al 1994). Studies suggest that ethnic minority and immigrant clients are less likely to selfdisclose with a Caucasian provider due to fears of discrimination and unfair treatment (Chang and Berk 2009) and more likely to disclose willingly to racially similar providers (Helms and Carter 1991;Thompson et al 2004).…”
Section: Intentions To Seek Professional Helpmentioning
confidence: 99%